Protocolo de Manchester na atenção primária à saúde: visão de profissionais, usuários e gestores - Danielle de Araújo Moreira (2014)
The present study is aimed at understanding the point of view from professionals, users and managers of the Manchester Triage System in Primary Health Care in the city of Sarzedo, located in the metropolitan area of Belo Horizonte, Minas Gerais. The study consisted of seven nurses, eleven nursing technicians, four doctors and seventeen users; bringing the total of 39 participants. The participants were divided into two groups: the primary one - nurses; and the secondary one nursing technicians, doctors and users. This research was approved by the Ethics Committee of UFMG (protocol number: 535.523) and by the Health Secretariat of Sarzedo, made through concession letter. It is a qualitative approach research, in which data collection was carried out within the months of March and May in 2014. Observation and a semi-structured survey questionnaire were used in the interview only after its participants consent and their signature on the Informed Consent Form (ICF). In order to do the data analysis, it was used the content analysis technique proposed by Bardin (2009). The results were organized into three categories: Understanding the use and the implantation of the Manchester Triage System in Primary Health Care; Manchester Triage System in Primary Health Care and in Emergency Services- It works perfectly for the Emergency Care, but in Primary Care it doesnt work at all; Manchester Triage System in Primary Health Care the view from the one who is being assisted. The data analysis allowed us to identify the challenges and potentialities that permeate the use of the Manchester Triage System in Primary Health Care. The participants stressed the importance of establishing criteria when it comes to the users risk classification for the ones who look for assistance in a Primary Care level. However, they also criticized the system and regarded it as insufficient, once it was developed to meet the Urgency and Emergency needs. According to the professionals outlook, it is impracticable to adopt a classification conduct that cannot be effectuated, after all, unlike the services which the Manchester Triage System was created, the MTS professionals deal with a working schedule that does not match the waiting time standard established for the triage. Moreover, the nurses pointed out another important aspect- the implementation of the risk classification by the Manchester Triage System affects the recommended actions for a primary level of assistance. The nurses stated that the implantation of the MST affected not only the bonds between professionals and patients, but also the qualified listening, the resolution of demands that exceed the diagnosis questions and the discriminators listed by TRIUS. Despite understanding that the risk classification disrupts the queuing system and the first-come first-served basis, the professionals also emphasized that the core of Primary Health Care, presented in the patients embracement, is being neglected. The potentialities mentioned by the participants consisted in the support provided by the MTS, for it has electronic documents that prove the conducts which were held. Then, it may bring the possibility of classifying the users by their medical conditions so as to establish priorities, organize patients assistance and disrupt the first-come first-served attendance/lines. In the users point of view, the triage consists of a useful tool to prioritize the most serious cases that demand a more urgent care. On the other hand, they also criticized the delays on receiving assistance and the scheduling of medical appointments. The study enabled the understanding that the use of the Manchester Triage System in Primary Health Care leads to gaps that need to be broken in order to ensure the continuity of the principles that conduct professional practice in this level of assistance. The Primary Health Care nurses should be attentive to each individuals need and comprehend that the act of getting sick can be expressed and understood in many different ways by the users. The important thing is that the risk classification should be guided in the patients embracement, in being with each other and in a moment of encounters, bonds and care.